Cosmetic and Reconstructive Breast Surgery in Adolescents: Psychological, Ethical, and Legal Considerations - Crerand, Canice E.; Magee, Leanne (Seminars in Plastic Surgery, 2013)
Cosmetic and reconstructive breast surgery has increased in popularity among adolescents in the United States. As more adolescents pursue these procedures, an understanding of the psychological aspects of these surgeries becomes increasingly important for the benefit of both patients and providers. The authors review the psychological aspects of cosmetic and reconstructive surgical breast procedures as they pertain to adolescents, including augmentation mammoplasty, gynecomastia correction, breast reduction, and asymmetry correction. They include a discussion of the medicolegal and ethical implications of these procedures and recommendations for clinical management.
Keywords: plastic surgery; breast; adolescence; psychosocial outcomes; ethics